The postwar Canadian housing and residential mortgage markets and the role of government - Smith, Lawrence Berk. (Toronto : University of Toronto Press, 1974)
The mortgage as important determinant of cyclical behavior of new residential construction.
Includes bibliographical references.
sju 22/01/2019
Loans
Keywords: Housing; Mortgage loans